DETERMINANTS OF REGIONAL ORIGINAL REVENUE AND ITS IMPACT ON REGIONAL INDEPENDENCE IN BANTEN PROVINCE - Fadhilla, Aulia Mitha; Setiyawati, Hari (Ridwan Institute, 2025)
The study aims to examine the influence of taxpayer compliance, organizational culture, and organizational commitment on local revenue, as well as its impact on regional independence in Banten Province. The data analysis in this study uses a quantitative analysis method with the analysis tool used is Partial Least Square-Path Modeling (PLS-PM 3.0). The results of this study show that there is a significant positive influence of regional taxpayer compliance with regional original income. The coefficient of the path parameter obtained a path coefficient value of 0.012 significantly at 2.068 > t-table 1.96 and a p-value of 0.000 a significance level of 0.05, which states that there are significant positive influences of regional tax compliance with the original income of the region. Organizational commitment has no effect on the original regional income. This study provides valuable insights for policymakers and local government officials on the importance of fostering a culture of compliance and commitment within organizations to enhance financial performance. The findings also add to the existing literature on public finance and governance, highlighting the interconnectedness of taxpayer behavior and organizational dynamics in achieving fiscal independence at the regional level.